Estudio y manejo de la caminadora (Rottboellia cochinchinensis) Lour W.D. Clayton en el Pacífico Seco de Costa Rica - Rojas, C.E.=700 1 De la Cruz, R.; Shannon, P.J.; Merayo, A.
Sumario (En)
Ilus.; 3 ref.
Keywords: ROTTOBOELLIA COCHINCHINENSIS; MALEZAS; ESCARDA; COSTA RICA